The Effect Of Trust As A Mediating Variable Of Social Media And E-Service Marketing On Purchase Decisions At Tiktok Shop - Siboro, Sonny Fransisco; Siregar, Otto; Sugeng, Irwin Sukrisno (Jurnal Scientia, 2024)
This research aims to analyze the role of trust as a mediating variable in the relationship between social media marketing and e-service quality on purchasing decisions at the TikTok Shop. Using a quantitative approach, data was collected from TikTok Shop users through an online survey which was distributed to 97 people. The data analysis technique used is path analysis to test the direct and indirect relationship between social media marketing, e-service, trust and purchasing decisions. The research results showe-servicepositive and significant effect on trust, e-service has a positive and significant effect on purchasing decisions, trust has a positive and significant effect on purchasing decisions, social media marketing has a positive and significant effect on trust, social media marketing has a positive and significant effect on purchasing decisions, trust can mediates e-service on purchasing decisions, while trust cannot mediate social media marketing on purchasing decisions.These findings emphasize the importance of effective social media marketing strategies and quality management services in building consumer trust, which ultimately drives purchasing decisions.